Kings rising - Pacat, C. S. (Pacat, C. S. Captive prince trilogy, 2016)
"His identity now revealed, Damen must face his master Prince Laurent as Damianos of Akielos, the man Laurent has sworn to kill...Forced into an uneasy alliance the two princes journey deep into Akielos, where they face their most dangerous opposition yet. But even if the fragile trust they have built survives the revelation of Damen's identity can it stand against the Regent's final, deadly play for the throne?"--Provided by publisher.